X(p-6) = z-8 => x = (z-8)/(p-6) if p≠6
Answer:-170
Step-by-step explanation:as you can see it is going in a pattern from the negative ok thanks.
Make/Model:
Ford E-Series Wagon Van
<span>MSRP: </span>
$28,760
<span>Cost of options: </span>
$5,560
<span>Sales tax: </span>
$2230.80 (this is based on 6.5% interest)
<span>Total cost: </span>
$36550.80
<span>10% down payment: </span>
$3655.08
<span>Amount needed to borrow: </span>
$32895.72
<span>Monthly payment: </span>
$665.62
<span>Total interest paid: </span>
$4,665.51
Total payments:
<span>60 payments of total $39,937.03</span>
Answer:
A man borrows * 8000
He agrees to repay with a total interest of 1360 in 12 monthly instalments.
Each instalment being less than the preceding one by * 40
=
x 40
= 12 x 34
= 408 (Ans)
I think the answer is 4/12 or 1/3